If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8k + -2(k + 7) = 15 + -6k Reorder the terms: 8k + -2(7 + k) = 15 + -6k 8k + (7 * -2 + k * -2) = 15 + -6k 8k + (-14 + -2k) = 15 + -6k Reorder the terms: -14 + 8k + -2k = 15 + -6k Combine like terms: 8k + -2k = 6k -14 + 6k = 15 + -6k Solving -14 + 6k = 15 + -6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '6k' to each side of the equation. -14 + 6k + 6k = 15 + -6k + 6k Combine like terms: 6k + 6k = 12k -14 + 12k = 15 + -6k + 6k Combine like terms: -6k + 6k = 0 -14 + 12k = 15 + 0 -14 + 12k = 15 Add '14' to each side of the equation. -14 + 14 + 12k = 15 + 14 Combine like terms: -14 + 14 = 0 0 + 12k = 15 + 14 12k = 15 + 14 Combine like terms: 15 + 14 = 29 12k = 29 Divide each side by '12'. k = 2.416666667 Simplifying k = 2.416666667
| 100+12h=23h+h | | -18-a=-25 | | 8(x-1)=4(x+2)-x | | 4(5x+4)=20x+16 | | (13x)-4=(x-8) | | 3(x+1)-5=3x-3 | | 7-(4y-3)=4-5y | | .20x+.45(70)=45.5 | | x^2-6x-230=0 | | 1.3t+3(t+8.2)=375 | | 7t+8t=45 | | 2(2r+5)+1=5-3(3-r) | | 4(x-1)=2(x+2)-x | | 5v=-2v-3v | | -4y-12=3y+16 | | 9(x+8)=8(x-8)+x | | 5(1+4x)=2(3+10x) | | 2(n-4)=4(5-2n) | | 11x-21=8x | | w-4(w+2)=7-2w | | n^2-12+4n+11=76 | | 4a^2b^2-5ab= | | 13+7x=9+15x | | X*x+x+3=196+x-4 | | 50x^2=32 | | 4(3z-5)=8 | | 4(2/5)+k=-32/11 | | -1.32=3(1.5x-0.5) | | x^2-6y+y^2-7=0 | | 4.5x^2-9x+3.5=0 | | 8y-2=-6y+50 | | -10=2+2.4w |